The function of the complement system remains fully intact throughout the course of allogeneic stem cell transplantation - Fageräng, Beatrice; Cyranka, Leon; Schjalm, Camilla; McAdam, Karin Ekholt; Larsen, Carina Sandem; Heinzelbecker, Julia; Gedde-Dahl, Tobias; Würzner, Reinhard; Espevik, Terje; Tjønnfjord, Geir Erland; Garred, Peter; Barratt-Due, Andreas; et al. (Frontiers in Immunology, 2024)
Hematopoietic stem cell transplantation (HSCT) is associated with immune complications and endothelial dysfunction due to intricate donor-recipient interactions, conditioning regimens, and inflammatory responses. This study investigated the role of the complement system during HSCT and its interaction with the cytokine network. Seventeen acute myeloid leukemia patients undergoing HSCT were monitored, including blood sampling from the start of the conditioning regimen until four weeks post-transplant. Clinical follow-up was 200 days. Total complement functional activity was measured by WIELISA and the degree of complement activation by ELISA measurement of sC5b-9. Cytokine release was measured using a 27-multiplex immuno-assay. At all time-points during HSCT complement functional activity remained comparable to healthy controls. Complement activation was continuously stable except for two patients demonstrating increased activation, consistent with severe endotheliopathy and infections. In vitro experiments with post-HSCT whole blood challenged with Escherichia coli, revealed a hyperinflammatory cytokine response with increased TNF, IL-1, IL-6 and IL-8 formation. Complement C3 inhibition markedly reduced the cytokine response induced by Staphylococcus aureus, Aspergillus fumigatus, and cholesterol crystals. In conclusion, HSCT patients generally retained a fully functional complement system, whereas activation occurred in patients with severe complications. The complement-cytokine interaction indicates the potential for new complement-targeting therapeutic strategies in HSCT.